Overcoming Barriers to Entry in an Established Industry: Tesla Motors. (August 2015) - Stringham, Edward Peter; Miller, Jennifer Kelly; Clark, J.R.
The automobile industry's high costs of entry, economies of scale, and network effects from distribution, fueling, and service lead many to conclude that new entrants have no chance. Tesla Motors has overcome many barriers to pioneer electric cars. Starting with partnerships and a minimum viable product, Tesla is working to innovate and scale up. Tesla now produces a top-selling luxury car and has a market capitalization twice that of Fiat Chrysler and half that of General Motors or Ford. Tesla has shown that a startup can enter and disrupt the status quo in one of the most established industries.